Voxel-Based Morphometric Comparison Between Early- and Late-Onset Mild Alzheimer’s Disease and Assessment of Diagnostic Performance of Z Score Images - Ishii, Kazunari; Kawachi, Takashi; Sasaki, Hiroki; Kono, Atsushi K; Fukuda, Tetsuya; Kojima, Yoshio; Mori, Etsuro (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Voxel-based morphometry (VBM), used for detecting brain atrophy, permits comparison of local gray matter concentration at every voxel in an image between two groups. We sought to delineate the specific patterns of cerebral gray matter loss with regard to onset of Alzheimer’s disease (AD) by using MR imaging and VBM and to evaluate the diagnostic performance of VBM with Z score images.METHODS: Two groups of 30 patients with mild AD of different ages of onset were examined. Mean ages in the early- and late-onset groups were 60.2 ± 5.2 and 71.5 ± 2.6 years, respectively. Control subjects were aged-matched healthy volunteers. Regions of gray matter loss in early- and late-onset AD were examined with VBM. Diagnostic performance of Z score images obtained with the VBM method was evaluated in patients and control subjects by calculating the area under the receiver operating characteristic curve (Az).RESULTS: Both AD groups had significantly reduced gray matter in the bilateral medial temporal regions. In addition, the early-onset group had more severe gray matter loss in the bilateral parietal and posterior cingulate cortices and precuneus region. No difference was noted in diagnostic performance of Z score images between the early- (Az = 0.9435) and late-onset (Az = 0.9018) groups.CONCLUSION: Differences were noted in the patterns of regional gray matter loss in patients with early-onset AD versus those with late-onset AD. Parietotemporal and posterior cingulate gray matter loss was found in early-onset AD but not in late-onset AD. Z score images obtained with VBM had a great diagnostic performance for mild AD and can be applied for detecting mild AD in clinical examinations.